Algeria : Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2011)
This statistical appendix on Algeria was prepared by a staff team of the International Monetary Fund as background documentation for the periodic consultation with the member country. Basic economic and financial indicators, sectoral distribution of GDP, and real GDP growth are listed. Production exports and consumption of petroleum and gas products are given. A summary of central government operations, revenue, and expenditure are also explained. The structure of interest rates and balance of payments are tabulated. Hydrocarbon export and trade indices are shown.